Obstructive Sleep Apnea Masquerading as Diabetic Retinopathy: A Case Report - Wei, Zhangwanyu; Zhang, Yongpeng; Yu, Weihong (American Journal of Translational Medicine, 2024)
BACKGROUND: Obstructive sleep apnea (OSA) is a chronic sleep-related breathing disorder causing intermittent nocturnal hypoxemia. OSA is associated with many ocular diseases, such as primary open-angle glaucoma, non-arteritic ischemic optic neuropathy, retinal vein occlusion, central serous chorioretinopathy, diabetic retinopathy, and age-related macular degeneration. CASE PRESENTATION: Here, we report on a patient with microaneurysms and retinal hard exudates for 10 years. The patient was suspected to have diabetic retinopathy but denied a history of diabetic mellitus and had normal blood sugar levels. Finally, based on his history of OSA and systemic atherosclerosis, we determined that his retinal changes were related to OSA. CONCLUSION: The present case of OSA, which was misdiagnosed as diabetic retinopathy for a decade, serves as a reminder not to overlook ocular manifestations of systemic diseases.